Early Targets of nRNP Humoral Autoimmunity in Human Systemic Lupus Erythematosus - Poole, Brian D. (2009)
OBJECTIVE: The U1 small nuclear ribonucleoproteins (nRNPs) are common targets of autoantibodies in lupus and other autoimmune diseases. However, the etiology and progression of autoimmune responses directed against these antigens are not well understood. Using a unique collection of serial human samples from before and after nRNP antibody development, we investigated early humoral events in the development of anti-nRNP autoimmunity. METHODS: Lupus patients with sera available from both before and after nRNP antibody precipitin development were identified from the Oklahoma Clinical Immunology Serum Repository. Antibodies in the serial samples were analyzed by ELISA, Western blotting, solid-phase epitope mapping and competition assays. RESULTS: The first detected nRNP antibodies targeted 6 common initial epitopes in nRNP A, 2 in nRNP C and 9 in nRNP 70K. The initial epitopes of nRNP A and nRNP C were significantly enriched for proline (p=0.0004, p=0.048) and shared up to 95% sequence homology. The initial nRNP 70K humoral epitopes differed from nRNP A and C. The initial antibodies to nRNP A and nRNP C were cross-reactive with the Sm B′-derived peptide PPPGMRPP. Antibody binding against all three nRNP subunits diversified significantly over time. CONCLUSIONS: nRNP A and nRNP C autoantibodies initially targeted restricted, proline-rich motifs. Antibody binding subsequently spread to other epitopes. The similarity and cross-reactivity between the initial targets of nRNP and Sm autoantibodies identifies a likely commonality in etiology and a focal point for intermolecular epitope spreading.